2017
DOI: 10.1080/08003831.2017.1390662
|View full text |Cite
|
Sign up to set email alerts
|

Farmer-fishermen: interior lake fishing and inter-cultural and intra-cultural relations among coastal and interior Sámi communities in northern Sweden AD 1200–1600

Abstract: Although the productive fishing grounds had long attracted the Crown and the Church to northern Sweden, it was not until the sixteenth century that the judicial and fiscal powers of the Swedish Crown were exercised in full. Records show that the regular fishing in interior lakes formed a prominent enterprise among coastal farmer communities. This paper examines the social and economic context of farmers engaged in interior fishing with respect to the internal organization of village communities, principles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…This required the isotopic characterization of various food groups which were likely to have contributed to the diet of the Rounala individuals. From historical sources, it is known that fish were an important dietary input, also for the people in Rounala (Nickul 1977:3, 10, 15, 32; Ruong 1982:22–26; Fjellström 1985:22–44; Korpijaakko-Labba 1994:81–86, 91–93; Bergman and Ramqvist 2017). In northern Scandinavia there are many lakes and large rivers from which freshwater fish would have been caught.…”
Section: Discussionmentioning
confidence: 99%
“…This required the isotopic characterization of various food groups which were likely to have contributed to the diet of the Rounala individuals. From historical sources, it is known that fish were an important dietary input, also for the people in Rounala (Nickul 1977:3, 10, 15, 32; Ruong 1982:22–26; Fjellström 1985:22–44; Korpijaakko-Labba 1994:81–86, 91–93; Bergman and Ramqvist 2017). In northern Scandinavia there are many lakes and large rivers from which freshwater fish would have been caught.…”
Section: Discussionmentioning
confidence: 99%
“…Recent archaeological research has revealed that very little in the coastal archaeological evidence suggests that colonists would have formed a significant part of the coastal communities prior to the 16th century (for an in-depth analysis see Kuusela et al 2016; see also Bergman and Ramqvist 2017). Neither the coastal-nor inland communities were agricultural societies during this timethis is reflected both in the site distribution patterns and artefactual evidence of which the former indicates a marine/riverine subsistence economy for the coastal-, and hunter/fisher economy for the inland communities (Kuusela 2013, 89-118) whereas the artefactual evidence in the north is devoid of agricultural implements which are prevalent in the southamong the assumed centres of the colonisation of the northern coastal zone (Kuusela 2015, 16-18;Kuusela et al 2016, 181-183).…”
Section: Northern Fennoscandiamentioning
confidence: 99%
“…These fisheries continued to be exploited through the millennia, not least in northern Europe. Artisanal fishing was of great importance in the historic period for the Sami [ 72 ], whose specialised fisher-hunter-forager cultures existed until recently along northern rivers and larger lakes in Sweden and in Finland. The Fisher-Sami fished the lakes of Tjäurajaure and Tjieggelvas in Swedish Lapland [ 73 ] and the Inari Sami were predominately fishermen in Lake Inari in northern Finland until recently.…”
Section: Resultsmentioning
confidence: 99%